PENERAPAN METODE MUHASABAH DALAM PEMBINAAN KARAKTER BAGI SISWA GENERASI Z - Dingot Hamonangan Ismail; Retno Widowati; Damdam Damiyana; Redjeki Agoestyawati Agoestyawati; Syubli Abbas; Ria Estiana (JURNAL ABDIMAS PLJ, 2023)
In the teaching and learning process, there are three aspects of ability that are targeted, namely knowledge, attitudes, and skills. The balance between these three aspects requires serious attention from teachers and all related parties in schools or in educational institutions. Students are nurtured and educated not only as intelligent, but at the same time have good social sensitivity, morals/character and religion, so that students are born as a religious generation. To achieve these educational goals with religious nuances, teachers are expected to be able to deliver students who have the intelligence to understand good morals through setting an example by showing good behavior so that students can emulate and apply it in everyday life. School is a place of learning for children. The purpose of the school itself is to teach about teaching students to become students who are able to advance the nation. In schools there is interaction between students and their teachers, which is called the teaching and learning process. In the teaching and learning process, of course, it does not always run smoothly or efficiently, but there are also problems encountered in learning, as well as for students at school, of course there are many obstacles or problems faced by students. This happens due to several factors besides that the attitudes and behavior of each student are of course different so that it can cause problems at school whether studying or not. The series of service activities is carried out in three stages. The first stage is observation where universities pay visits to SMKN 16 Jakarta to identify problems that occur in student character during the learning process at school. The second stage is carrying out activities for providing material and muhasabah for students, while the third stage is the evaluation stage related to the implementation of community service.Keyword: character building, muhasabah, generation Z